2002
DOI: 10.1038/sj.ejcn.1601366
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and serum α-tocopherol, β-carotene and retinol, and risk for colorectal cancer in male smokers

Abstract: Objective: To study the association between dietary and serum antioxidant vitamins and carotenoids and risk for colorectal cancer in male smokers. Design: A prospective cohort study within a randomised, double-blind, placebo-controlled trial testing supplementation with atocopherol (50 mg=day), b-carotene (20 mg=day) or both in preventing cancer. Subjects and methods: Participants of the Alpha-Tocopherol, Beta-Carotene Cancer Prevention Study with complete dietary data and serum samples available from baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 33 publications
3
47
0
6
Order By: Relevance
“…Two prospective studies observed no association with CRC for carotenoids and tocopherols, although a pooled analysis of five cohort studies on atocopherol suggested a slight inverse association. 10,12,13 An inverse association with CRC has also been reported for circulating retinol in one of three previous studies. [10][11][12] The large number of cases in this study is one of its great strengths, together with the prospective design and information on a wide range of confounders.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Two prospective studies observed no association with CRC for carotenoids and tocopherols, although a pooled analysis of five cohort studies on atocopherol suggested a slight inverse association. 10,12,13 An inverse association with CRC has also been reported for circulating retinol in one of three previous studies. [10][11][12] The large number of cases in this study is one of its great strengths, together with the prospective design and information on a wide range of confounders.…”
Section: Discussionmentioning
confidence: 75%
“…10,12,13 An inverse association with CRC has also been reported for circulating retinol in one of three previous studies. [10][11][12] The large number of cases in this study is one of its great strengths, together with the prospective design and information on a wide range of confounders. It is possible that previous studies were unable to detect associations with CRC or subsite-specific associations, because of the low number of included cases (ranging from 88 to 184).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The between-run coefficients of variation were 2.2% for a-tocopherol, 3.6% for h-carotene, and 2.4% for retinol (21).…”
Section: Methodsmentioning
confidence: 96%
“…Dazu gehören Kalzium, Magnesium, β-Carotin, Vitamin A, C, D, E, Folsäure und Selen [36]. Im Fall von Vitamin A und C sah die Leitliniengruppe keinen eindeutigen Beleg für eine Senkung des KRK-Risikos durch eine regelmäßige Einnahme des Vitamins [21,32,37,38]. Für Vitamin D ist die Datenlage ebenfalls unzureichend, um eine sichere Aussage über einen möglichen protektiven Effekt treffen zu können [32,[37][38][39].…”
Section: Vitamine Und Mikronutrientsunclassified